GUIDELINES FOR ENHANCING EDUCATIONAL RESOURCES IN THE DIGITAL AGE OF FUJIAN UNIVERSITY OF TECHNOLOGY IN FUJIAN PROVINCE PEOPLE'S REPUBLIC OF CHINA - Sewlong, Yew; Kawsrimol, Boranajit; Suteeniran, NIran; Dechome, Pachara; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2023)
The purpose of this research were to 1) study the enhancement of educational resources in the digital age 2) assess the characteristics of educational resources enhancement in the digital age. 3) study ways to enhance educational resources in the digital age. People's Republic of China with mixed method research consisting of 1) Human resources 2) Financial resources 3) Materials, equipment and buildings resources 4) Management resources 5) Time resources 6) Information technology resources The research population was Fujian University of Technology in Fujian Province, People's Republic of China. The samples used in this study were administrators and lecturers at Fujian University of Technology in Fujian Province. People's Republic of China by specific random sampling, totaling 242 people.The research results showed that enhancing educational resources in the digital age of Fujian University of Technology in Fujian Province. People's Republic of China Management must support and have a good attitude towards the use of information systems Encourage development to always be efficient depending on the situation and conditions that occur Encourage personnel to have a good attitude in work. Encourage appropriate financial behaviors. Administrators can arrange the environment in educational institutions to facilitate the performance of personnel. Encourage personnel to have love and unity with each other, to be able to organize activities on the work calendar that are in line with the agency's financial system. and achieve maximum efficiency for educational institutions. Covers organizational management goals for excellence based on knowledge management and technology. Organizational development that focuses on quality human resources in creating organizational plans and strategies that meet international standards.